A new derivatizing method for the simultanous determination of 3-monochloropropanediol and 1,3- dichloropropanol in heat processed food samples / Lee Bai Qin - Lee , Bai Qin (2017)
3-Monochloro-1,2-propanediol (3-MCPD) and 1,3-dichloropropanol (1,3-DCP) are heat- produced contaminants that form during the acid hydrolysis of vegetable protein (acid-HVP), which is a process employed in the production of artificial soy sauces. Available laboratory study reports have shown that 3-MCPD is carcinogenic and toxic to the kidneys and reproductive organs, while 1,3-DCP is genotoxic, hepatotoxic and carcinogenic. On account of the carcinogenic properties reported, 3-MCPD and 1,3- DCP are listed as Proposition 65 (Prop. 65) and group 2B carcinogens. The Association of Official Analytical Chemists (AOAC) method of 3-MCPD detection requires highntemperature heating (60°C) and a costly derivatizing agent (61.10 USD mL-1 ), heptafluorobutyrylimidazole (HFBI). The purpose of this study is to develop an alternative to the current methods of detecting and quantifying 3-MCPD and 1,3-DCP, especially in complex food matrices. Therefore, the focus of this study is on developing a cost and time-efficient procedure to detect 3-MCPD and 1,3-DCP simultaneously at room temperature (25C). Silylation derivatizing agent Hexamethyldisilazane (HMDS) coupled with the catalyst Trimethylsilyl trifluoromethanesulfonate (TMSOTf) are used to derivatize 3-MCPD and 1,3-DCP. Box-Behnken simulation and point-to-point optimization are applied to optimize the developed derivatization process. An actual food sample analysis based on the Student’s T- test analysis indicates there is no significant difference between the HFBI and HMDS derivatization methods used for 3-MCPD and 1,3-DCP quantification. The newly established derivatization method is applied to identify and quantify 3-MCPD and 1,3-DCP found in commercially available soy sauces, thick sauces and flavored seasonings sold in Malaysia. The determined concentrations are compared with the Malaysian Adult Nutrition Survey (MANS) to investigate Malaysians’ daily exposure to 3-MCPD and 1,3-DCP. In conclusion, this study introduces a cost-efficient derivatizing agent to quantify 3-MCPD and 1,3-DCP, and to establish a database of Malaysians’ daily exposure to 3-MCPD and 1,3-DCP with a risk assessment.